Thin-shell Solution of Chameleon Mechanism in Brans-Dicke Scalar-Tensor Model - Azwar Sutiono; Agustina Widiyani; Marliana Marliana; Getbogi Hikmawan; Agus Suroso; Freddy Permana Zen (Institut Teknologi Bandung, 2022)
We investigated the chameleon screening mechanism in Brans-Dicke scalar-tensor theory. We preserved the fundamental premise of the typical chameleon mechanism, which is that the field is huge in high-density environments but essentially free in low-density environments like the solar system. We discovered thin-shell solutions for a static and spherical symmetric body and demonstrated the model’s applicability to local data.